A history of the Second World War in 100 maps - Black, Jeremy 1955- (The University of Chicago Press, 2020)
"Assembled by the same team responsible for A History of America in 100 Maps by Susan Schulten, this book offers a selection of 100 maps, all presented in full color, that shaped the course of World War II. Alongside the maps, historian Jeremy Black offers context and explanations drawing on his long career thinking about war and maps. World War II was a uniquely difficult war to map: it was fought across an unprecedented geographical range, through the air as well as by land and sea, and at a faster tempo than any previous conflict. Creating maps for the military to use as tools, as well as for governments and others to use in spreading their messages about the war, presented new challenges to mapmakers. But the development of new technologies such as aerial photography and all-weather instrument flying aided their efforts, and the scale of map production during the war was astonishing. The maps in this book are drawn from the British Library's collections as well as other sources across the world and organized thematically. In addition to military operations, tactics, and strategy on all sides, the maps illustrate the geopolitical context for war as well as reporting and propaganda efforts by the Allies and the Axis countries during and after the war"